COVID-19 Pandemic and Performance of Indonesian Stock Market: An Event Study Analysis - Andhyka Tyaz Nugraha; Yusro Hakimah; Agung Masyad Fawzi (Jurnal Economia, 2022)
AbstractThe aims of study are to analyze and evaluate the impact of COVID-19 outbreak on Indonesia Stock Exchange (IDX) performance before, during, and after the official announcement day on March 2nd, 2020. Five industry sectors were observed, i.e agriculture, property, manufacture, consumer, and mining sector. Event study analysis method is used to value the short-term influence of the announcement day on the selected stock market performance in Indonesia. The findings of the study indicated that manufacturing and consumer sectors had better stock performance with positive results of their abnormal return, unlike the agriculture and property sectors which showed the opposite result of their stock performance. The stock performance in the mining sector remained stable even after the announcement day. Indonesian Government, particularly the companies’ management, is expected to pay more attention to the aggrieved industries because of the negative effect of outbreaks, especially on the agriculture and property sector. Keywords: COVID-19, Event Study, Abnormal Return, Stock Performance, Indonesia Stock Exchange Pandemi COVID-19 dan Kinerja Pasar Saham Indonesia: Analisis Studi Peristiwa AbstrakPenelitian ini bertujuan untuk menganalisis dan mengevaluasi dampak wabah COVID-19 terhadap kinerja Bursa Efek Indonesia (BEI) sebelum, selama, dan setelah hari pengumuman resmi pada tanggal 2 Mei 2020. Lima sektor industri yang diamati yaitu sektor pertanian, properti, manufaktur, konsumen, dan pertambangan. Kami menggunakan metode analisis studi peristiwa dalam penelitian ini untuk menilai pengaruh jangka pendek hari pengumuman terhadap kinerja pasar saham terpilih di Indonesia. Hasil studi empiris menunjukkan bahwa sektor konsumen dan manufaktur memiliki kinerja saham yang lebih baik dengan hasil yang positif dari abnormal return-nya, tidak seperti sektor properti dan pertanian yang menunjukkan hasil sebaliknya dari kinerja sahamnya. Kinerja saham di sektor pertambangan tetap stabil bahkan setelah hari pengumuman. Pemerintah Indonesia, khususnya manajemen perusahaan, diharapkan lebih memperhatikan industri yang dirugikan akibat dampak negatif wabah, terutama pada sektor pertanian dan properti. Kata kunci: COVID-19, Studi Peristiwa, Abnormal Return, Kinerja Saham, Bursa Efek Indonesia.